Pneumonia in newly diagnosed patients infected with the Omicron variant: a population-based study of Chinese patients in Chongqing - Jing Guo; Jian Xiong; Yajuan Chen; Huyu Wang; Rouqian Chen; Lili Shui (BMJ Open Respiratory Research)
Background Pneumonia is the main complication of the Omicron variant of SARS-CoV-2; however, the incidence proportions and prognostic factors for Omicron-associated pneumonia have not been established. We conducted this study to characterise the incidence proportions and influence of various factors on prognosis of Omicron-associated pneumonia.Methods We collected data from 714 patients infected with the Omicron variant in The First Affiliated Hospital of Chongqing Medical University (Chongqing, China) who were divided into different groups for analysis.Results We identified 313 patients with Omicron-associated pneumonia at the time of diagnosis of patients infected with the Omicron variant, representing 43.8% of the entire cohort. A total of 82 were 15–59 years old, 71 were 60–69 years old, 76 were 70–79 years old and 84 were >80 years old. 133 were female and 180 were male. Incidence proportions of pneumonia were highest among patients with cardiovascular (82.4% of the basic disease of the cardiovascular system subset) or kidney disease (92.3% of the kidney disease subset), whereas patients with lung cancer (35.7% of the lung cancer subset) had a lower incidence proportion. Several factors were associated with the prognosis of pneumonia in patients infected with the Omicron variant. Patients with a thrombosis or pleural effusion had a longer hospitalisation time. Paxlovid and immunoglobulins improved the prognosis of patients with severe pneumonia. The following measures were significantly different in patients as a function of disease severity: number of neutrophils and lymphocytes, partial oxygen pressure; and myoglobin, lactic dehydrogenase, aspartate transaminase and procalcitonin levels.Conclusion Patients infected with the Omicron variant with coexisting cardiovascular or kidney disease, but not respiratory disease, had a higher incidence proportion of pneumonia. Paxlovid and immunoglobulins can be used in patients with severe infections to improve prognosis.